2017
DOI: 10.18240/ijo.2017.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual and topographic outcomes of deep-anterior lamellar keratoplasty and penetrating keratoplasty in keratoconus

Abstract: Big bubble DALK provides an earlier visual improvement compare to PK. However, visual and topographic outcomes are similar to those in PK at 1y. Postoperative complications including rejection and intraocular pressure elevation are more frequent in PK. DALK is a safer alternative to PK for KC. However, intraoperative perforation of the Descemet's membrane is a significant complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Nevertheless, anterior lamellar keratoplasty still has an advantage over PKP in terms of complications-lower risk of transplant rejection or secondary glaucoma. Further, new techniques using femtosecond laser may improve postoperative visual acuity in those patients [26][27][28][29]. Decrease in percentage of DALK was observed in our study, although keratoconus remained a second most frequent indication through all analyzed years.…”
Section: Plos Onesupporting
confidence: 54%
“…Nevertheless, anterior lamellar keratoplasty still has an advantage over PKP in terms of complications-lower risk of transplant rejection or secondary glaucoma. Further, new techniques using femtosecond laser may improve postoperative visual acuity in those patients [26][27][28][29]. Decrease in percentage of DALK was observed in our study, although keratoconus remained a second most frequent indication through all analyzed years.…”
Section: Plos Onesupporting
confidence: 54%
“…During DALK, the endothelium and Descemet membrane are separated from the corneal stroma through intrastromal air injection (big-bubble technique). 31 Yüksel et al 32 reported that big-bubble DALK results in earlier visual improvement than does PKP. However, at 1 year, the visual and topographic results are similar to those of PKP.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rates of postoperative complications such as graft rejection, secondary glaucoma, complicated cataracts, and constant endothelial cell loss are higher with PK. 135 , 161 , 162 , 163 , 164 , 165 , 166 …”
Section: Methodsmentioning
confidence: 99%